Ceramic Complex from the Excavations of the Gilevs Estate at the Intersection of Pushkin and Pervomaiskaya Streets in Ekaterinburg: A Technical and Typological Analysis and Morphology of the 19th – Early 20th Centuries Crockery - E. A. Bulakova; Yu. V. Vasina; E. A. Trofimova (Историко-географический журнал)
The article presents the results of a technical, typological and morphological analysis of a ceramic complex (crockery) obtained during excavations of a site of the cultural layer of the modern era (19th — early 20th centuries) within Pushkin – Pervomaiskaya – Tolmacheva streets in Ekaterinburg, which is the courtyard of the Gilevs burgher estate. It provides a detailed description of the stages of formation of the site itself and a biography of the inhabitants of the house from 1810/15 to 1912, as well as some data from archaeological work, a significant part of which is the analysis of the clothing complex. Dealing with such type of archaeological source, as archaeological ceramics, is of particular interest due to the limited data in written sources about the types and places of pottery production in Ekaterinburg from the late 18th to early 19th centuries. Describing and identifying the types of ceramics obtained, firstly, allows determining the crockery types and starting creation of a typology of the 19th — early 20th centuries dishes, used in everyday life by residents of the estate, and more broadly, the city. And, secondly, it allows combination and comprehensive analysis of data from written and archaeological sources. For Ekaterinburg, such work based on archaeological sources is relevant and interesting; it is presented in an expanded format for the first time.